Analyzing Psychotherapy on Twitter: An 11-Year Analysis of Tweets From Major U.S. Media Outlets - Alvarez-Mon, Miguel A.; Fernandez-Lazaro, Cesar Ignacio; Ortega, Miguel A.; Vidal, Cristina; Molina-Ruiz, Rosa M.; Alvarez-Mon, Melchor; Martínez-González, Miguel A. (Frontiers in Psychiatry, 2022)
Background: The Internet has become the main source of information on health issues, and information now determines the therapeutic preferences of patients. For this reason, it is relevant to analyze online information discussing psychotherapy. Objective: To investigate tweets posted by 25 major US media outlets between 2009 and 2019 concerning psychotherapy. Methods: We investigated tweets posted by 25 major US media outlets about psychotherapy between January 2009 and December 2019 as well as the likes generated. In addition, we measured the sentiment analysis of these tweets. Results: Most of the tweets analyzed focused on Mindfulness (5498), while a low number were related to Psychoanalysis (376) and even less to Cognitive-Behavioral Therapy (61). Surprisingly, Computer-supported therapy, Psychodynamic therapy, Systemic therapy, Acceptance and commitment therapy, and Dialectical behavior therapy did not generate any tweet. In terms of content, efficacy was the main focus of the posted tweets, receiving Cognitive-Behavioral Therapy and Mindfulness a positive appraisal. Conclusions: US media outlets focused their interest on Mindfulness which may have contributed to the growing popularity in the past years of this therapeutic modality.